Pengaruh Kualitas Produk, Citra Merek dan Promosi terhadap Keputusan Pembelian Honda Beat di Kota Denpasar - Afton Irawan Parmono; Putu Irma Yunita (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the influence of product quality, brand image, and promotion on purchasing decisions for Honda BeAT motorcycles in Denpasar City. This study uses a quantitative approach with a causality research design to test the causal relationship between variables. The sampling technique used was purposive sampling with a total of 150 respondents, namely Honda BeAT motorcycle users who have income and are domiciled in Denpasar City. Data collection was carried out through the distribution of structured questionnaires compiled using a five-point Likert scale to measure respondents' perceptions of the research variables. The data obtained were then analyzed using multiple linear regression methods to determine the influence of each independent variable on purchasing decisions, both partially and simultaneously. The results showed that product quality, brand image, and promotion had a positive and significant influence on purchasing decisions for Honda BeAT motorcycles. Partially, each variable has a real contribution in encouraging consumers to make purchases. Simultaneously, the three variables together have a significant influence on purchasing decisions. These findings indicate that improving product quality, strengthening positive brand image, and implementing effective promotional strategies are important factors in increasing consumer interest and purchasing decisions for the Honda BeAT in Denpasar City.